Mokilese Reference Grammar - Harrison, Sheldon (PALI Language Texts-Micronesia, 1976)
This is the first attempt to present for native speakers of Mokilese the essential features of the language. Written primarily for a lay audience with no prior knowledge of linguistics, this work will be useful as well to the professional linguist seeking data on a Micronesian language. The grammar covers the phonology, morphology, and syntax of Mokilese. Separate treatment is given to the nominal reference system, quantification and counting, possession, transitivity, modality, direction markers, verbal aspect, complex sentences, derivation, and questions of topicalization and focus. An appendix discusses problems in devising an orthography for Mokilese and the methodology employed.